Differential Diagnosis of Polypoid Lesions of the Gallbladder Using Contrast‐Enhanced Sonography. (1st June 2015) - Liu, Xue-Song; Gu, Li-Hong; Du, Jing; Li, Feng-Hua; Wang, Jian; Chen, Tao; Zhang, Yun-He
Abstract : Objectives: The purpose of this study was to evaluate the usefulness of real‐time contrast‐enhanced sonography and microvascular imaging for differential diagnosis of neoplastic and non‐neoplastic polypoid lesions of the gallbladder. Methods: Real‐time contrast‐enhanced sonography and microvascular imaging were performed in 128 patients with polypoid lesions of the gallbladder larger than 6 mm in diameter. The enhancement patterns, microvascular imaging types, and kinetic parameters were analyzed on contrast‐enhanced sonography. The maximum diameters of the lesions measured by conventional and contrast‐enhanced sonography were also recorded and subjected to a comparative analysis. Results: Among the 128 patients, histologic diagnoses were obtained in 83 (27 neoplastic lesions and 56 non‐neoplastic lesions), which constituted the study group. On contrast‐enhanced sonography, mild enhancement and absence of contrast were more easily found in non‐neoplastic lesions (12 [21.4%]), whereas all neoplastic lesions showed marked enhancement (27 [100%]; P = .006). Of the 27 neoplastic lesions, 6 malignant tumors showed a perfusion defect on contrast‐enhanced sonography, whereas none of the non‐neoplastic lesions showed a perfusion defect ( P = .003). The microvascular architecture of the lesions was categorized into 4 types: spotty, linear, branched, and spinous, and there were significant differences between the groups ( P < .001). In a kinetic evaluation, none of the parameters reached statistical significance (all P > .05). There was a discrepancy in maximum diameters between conventional and contrast‐enhanced sonography in both groups but the discrepancy was significantly greater in the non‐neoplastic group ( P = .026). Conclusions: Contrast‐enhanced sonography is a useful imaging technique and an adjunct to conventional sonography for differential diagnosis of neoplastic and non‐neoplastic polypoid lesions of the gallbladder.